Talking with pregnant women exposed to cannabis use after cannabis legalization: Experiences of professionals working in Québec's social and healthcare system - Karen A. Dominguez-Cancino; Rose Chabot; Yolaine Frossard de Saugy; Kristelle Alunni-Menichini; Lysiane Robidoux-Léonard; Genève Guilbert-Gauthier; Karine Bertrand; Christophe Huỳnh; Pablo Martínez; Helen-Maria Vasiliadis; Nadia L'Espérance; Victoria Massamba; et al. (SSM: Qualitative Research in Health)
Background: The rising prevalence of prenatal cannabis use in high-income countries presents a growing concern for the medical community. Despite guidelines outlining risks, healthcare and social service professionals often struggle to discuss cannabis use with pregnant women. This study examines how these interactions have evolved following the Cannabis Act in Québec, focusing on how professionals respond to and provide guidance for women who report cannabis use during pregnancy. Methods: This is a qualitative study using semi-structured interviews. Purposeful sampling was employed to recruit 19 professionals, including physicians, nurses, psychologists, and social workers. Data was analyzed using King's (2012) Template analysis technique. Results: We identified three themes: a) how professionals talk about cannabis, b) what they talk about, and c) what practices they follow. Two key processes—i) exploration and assessment, and ii) action—were identified. Professionals tailor interventions, including counseling, psycho-emotional management, harm reduction, and referrals, based on risk levels and willingness to change. We observed differences among professionals based on the programs in which they work. Conclusions: This study highlights the complex interactions between health professionals and pregnant women who use cannabis. It discusses the importance of integrating harm reduction strategies with person-centered approaches to address cannabis use. While professionals balance the need for openness with concerns about fetal health, a knowledge gap persists. Strengthening educational initiatives and expanding addiction expertise could enhance support and intervention practices, bridging gaps left by current evidence and regulatory frameworks.